Changes in the symptoms and ultrasound signs of achilles tendinopathy during a twelve week course of loaded eccentric training: a pilot study. Issue 2 (20th January 2011) - Jangra, A; Perry, M; Maffulli, N; Malliaras, P; Morrissey, D
Abstract : Background: 12 weeks of eccentric exercise has been shown to be a useful therapy for Achilles tendinopathy, but little is known of the time-course of recovery, or the nature of any structural changes during therapy. Objectives: To assess the time-course and pattern of Achilles tendon symptoms, thickness, stiffness, and ultrasound (US) signs during 12 weeks of eccentric exercise (EE). Methods: Five subjects of age range (mean) 38–52 (46) years with main-body AT were included. For each subject, serial measurements of VISA-A score, the presence of neovascularisation and grey-scale US signs within the tendon, and the thickness of the Achilles tendon at 3 points were recorded for the first three weeks of a twelve week EE programme. Results: Median VISA-A score increased from 48.5 to 54.5 (p=0.116). Median mid-tendon thickness decreased from 0.834 cm to 0.790 cm (p=0.107). A trend towards a decrease in tendon thickness was noted directly superior to the retrocalcaneal bursa and at the soleus myotendinous junction. Neovascularisation, paratenon blurring and hypoechoic areas improved in 1/3, 1/3 and 2/5 tendons respectively. No significant change occurred in median tendon stiffness. Conclusion: 3 weeks of EE do not produce significant changes in AT symptoms and tendon thickness or stiffness, but improve US signs and neovascularisation in some subjects. The non-significance of findings may be a type II error and further work with larger sample sizes is planned.